Tarpeia : Workings of a Roman Myth - Welch, Tara S., 1967-; Project Muse. (Columbus, Ohio : The Ohio State University Press, 2015)
According to legends of Rome's foundation, Tarpeia was a maiden who betrayed Romulus' city to the invading Sabines. She was then crushed to death by the Sabines' shields and her body hurled from the Tarpeian Rock, which became the place from which subsequent traitors of the city were thrown. In this volume, Tara S. Welch explores the uses and contours of Tarpeia's myth through several centuries of Roman history and across several types of ancient sources, including Latin and Greek texts in various genres. Welch demonstrates how ancient thinkers used Tarpeia's myth to highlight matters of ethics, gender, ethnicity, political authority, language, conquest, and tradition. This cluster of themes reveals that Tarpeia's myth is not primarily about what it means to be human, but rather what it means to be Roman. Thus Tarpeia's story spans centuries, distances, genres, and modes of communication--Rome itself did. No Greek city-state could admit such continuity, and Greece was never so constant. In this way, though Tarpeia has a dozen Greek cousins whose stories are similar to hers, hers is a powerfully Roman myth, even for the Greeks who told her tale. She is token, totem, and symbol of Rome.
The shape of variety: girl, city, Rome -- Part one: Tarpeia, ethnicity, and being Roman in the republic -- Fabius Pictor's greedy girl: not yet tota Italia -- Tarpeia in silver: the denarii of the social war -- Part two: Tarpeia and the Caesars: from republic to empire -- Varro's Vestal version: Tarpeia in word and stone -- Perspectives on and of Livy's Tarpeia -- Elegiac Tarpeia (who won't stay put) -- Valerius Maximus on remembering Tarpeia's memorable deed -- Part three: Tarpeia from the outside in: Greek sources and the Roman empire -- Hellenistic Tarpeia in the elegy of Simylus -- On the edge of the knife in Dionysius of Halicarnassus -- Songworthy Athens, invincible Rome: Tarpeia in Plutarch's Romulus.
Description based on print version record.
Keywords: Tarpeia -- (Mythological character); Tarpeia -- (Mythological character); Tarpeia -- (Mythological character); Mythology, Roman; LITERARY CRITICISM -- General; SOCIAL SCIENCE -- Folklore & Mythology; Mythologie romaine -- Histoire et critique; Mythology, Roman -- History and criticism; Criticism, interpretation, etc; Electronic books